2021
DOI: 10.1177/23780231211006977
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic Penalty: The Gendered Effects of COVID-19 on Scientific Productivity

Abstract: Academia serves as a valuable case for studying the effects of social forces on workplace productivity, using a concrete measure of output: scholarly papers. Many academics, especially women, have experienced unprecedented challenges to scholarly productivity during the coronavirus disease 2019 (COVID-19) pandemic. The authors analyze the gender composition of more than 450,000 authorships in the arXiv and bioRxiv scholarly preprint repositories from before and during the COVID-19 pandemic. This analysis revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
2
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 85 publications
5
120
2
6
Order By: Relevance
“…The next figures are TEU and TU personnel. However, the mean male workload in TEU (42) and TU (46) is lower than for females (47 and 49, respectively). The same pattern is found in CD: the mean male workload is 49, while it is 52 for females.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The next figures are TEU and TU personnel. However, the mean male workload in TEU (42) and TU (46) is lower than for females (47 and 49, respectively). The same pattern is found in CD: the mean male workload is 49, while it is 52 for females.…”
Section: Resultsmentioning
confidence: 88%
“…Other future line of research would be to analyze the possible consequence of COVID-19 pandemic in the workload of academic staff and changes in the distribution of activities. According to other approaches [41,42], the more time being spent on caregiving responsibilities during the COVID-19 pandemic has dropped female scientific productivity. Therefore, policies should also address this gendered effect [43].…”
Section: Discussionmentioning
confidence: 99%
“…Análisis cuantitativos indicaron que entre 2019 y 2020, el número de publicaciones realizadas por mujeres aumentó un 2,7%, mientras que las publicaciones realizadas por hombres se dispararon un 6,4%, indicando la persistente segregación de género en dicho ámbito (Frederickson, 2020), sobre todo en el campo de las ciencias exactas (King y Frederickson, 2021;Krukowsky, Jagsi y Cardel, 2021;Viglione, 2020).…”
Section: Introductionunclassified
“…Diversas autoras concluyen que, durante la pandemia, el acompañamiento escolar de las y los hijos, ha tenido incidencia directa en el decremento de la producción científica de las mujeres (Frederickson, 2020;King y Frederickson, 2021;Krukowsky, Jagsi y Cardel, 2021Viglione, 2020. El contexto de contingencia ha mermado la visión de la trabajadora ideal, visualizando los efectos de las responsabilidades domésticas adicionales, junto con el servicio desproporcionado, la enseñanza y el trabajo emocional (King y Frederickson, 2021).…”
Section: Introductionunclassified
“…Researchers have registered their concerns about the increase in or existence of research equalities during the COVID-19 pandemic. For instance, (King & Frederickson 2021;Muric et al 2021;Pinho-Gomes et al 2020) reported underrepresentation of women in the authorship, rst and last authorship positions of COVID-19 publications.…”
Section: Introductionmentioning
confidence: 99%